DOI: 10.1007/978-3-540-74591-4_8
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Formalisation of Finite Group Theory

Abstract: Une formalisation modulaire des groupes finis Résumé : Ce rapport présente une formalisation de théorie des groupesélémentaires réalisée dans le système Coq. Ce travail est la premièreétape d'un projet d'envergure, qui a pour but de construire une preuve formelle du théorème de Feit-Thompson. Comme nos développements formels ultérieurs reposeront de façon cruciale sur cette base, nous avons consacré un soin particulierà la modularité de ces fondations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…One of the key results, the Feit-Thomson (or odd-order) theorem (Feit and Thompson, 1963) takes 255 pages to itself. A formalization of the odd-order theorem has recently been started by the INRIA-Microsoft research project on "mathematical components" lead by G. Gonthier (Gonthier, Mahboubi, Rideau, Tassi and Thery, 2007). As another example, the preprint of F. Almgren's masterpiece in geometric measure theory, familiarly referred to as the "Big Paper", is 1728 pages long.…”
Section: Proofs and Programsmentioning
confidence: 99%
“…One of the key results, the Feit-Thomson (or odd-order) theorem (Feit and Thompson, 1963) takes 255 pages to itself. A formalization of the odd-order theorem has recently been started by the INRIA-Microsoft research project on "mathematical components" lead by G. Gonthier (Gonthier, Mahboubi, Rideau, Tassi and Thery, 2007). As another example, the preprint of F. Almgren's masterpiece in geometric measure theory, familiarly referred to as the "Big Paper", is 1728 pages long.…”
Section: Proofs and Programsmentioning
confidence: 99%
“…For our purposes, three classes of types are of particular importance. These are discrete types, countable types, and finite types [16].…”
Section: Type Theory Preliminariesmentioning
confidence: 99%
“…We integrated Théry's formalization of elliptic curves [30] in our framework, and showed that the set of points of the elliptic curve E a,b can be construed as a finite cyclic group, as defined in SSREFLECT standard library [19]; 2. We defined Icart function, and showed that it generates points in the curve E a,b .…”
Section: Application To Elliptic Curvesmentioning
confidence: 99%
“…The proof involves the various notions of equivalence we develop in this paper and is thus an excellent testbed for evaluating the applicability of our methods. Additionally, the proof builds on several large developments (including Théry's formalization of elliptic curves [30] and Gonthier et al formalization of finite groups [19]) and demonstrates that CertiCrypt blends well with large and complex mathematical libraries, and is apt to support proofs involving advanced algebraic and number-theoretical reasoning.…”
Section: Introductionmentioning
confidence: 95%